Modern and ancient glaciation of northern slope of the Tavan-Bogdo-Ola massif - I. G. Moskalenko; D. A. Ganyushkin; K. V. Chistyakov (Лëд и снег, 2015)
Dynamics of glaciation of the northern slope of Tavan-Bogdo-Ola in the period of 1962–2011 has been defined on basis of field observations and analysis of aerial photos. Glaciers of the first and of the second Late Neopleistocene glaciations, historical glacial stage and Little Ice Age (LIA) were reconstructed by geomorphologic methods. In 2009–2011 glaciation of the northern slope was represented by 12 glaciers with total area about 22 km². In the maximum of the first Late Neopleistocene glaciation the total area of the glaciers was 4 times larger than present, firn line depression was 620 m. In the maximum of the second glaciation it was 3 times larger than now, firn line depression was 460 m. In historical glacial stage the total area of glaciation was about 2 times larger than now, firn line depression was 170 m. In LIA the area of glaciation was 16 km² larger than now, the firn line was 125 m lower. From the maximum of the LIA till 1962 glaciers lost about 9,6 km² of its area, the level of firn line rose about 50 m. In 1962–2002 the loss of the glacial area was 3,2 km², in 2002–2009 – 3 km².